Strengthening women’s resilience and participation in climate governance in the agrifood sector through public policies: A Strategic Review - Mohammed, Kamaldeen; Najjar, Dina; Bryan, Elizabeth (2024)
This presentation was given at the Canadian Association of Geographers (CAG) 2024: 74th Annual Meeting & Conference, hosted at the Memorial University of Newfoundland from August 14 to 18, 2024.